ANALISA EFISIENSI EXERGI BOILER DI PLTU UNIT 3 PT. INDONESIA POWER SEMARANG – JAWA TENGAH - Musanta H. Ginting; MSK. Tony SU.; Khoiri Rozi (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2013)
In this paper, thermodynamic analysis in boiler which placed in Steam Power Plant (PLTU) Unit 3 UBP Semarang and has 200 MW capacities is presented. Thermodynamic analysis used in this paper is exergy analysis. Exergy analysis has function to identify the used of real energy or the quality result of the actual energy consumption and the real lost of energy as result from irreversible process. Exergy can have destruction from irreversible processes and the heat movement to environment. Boiler is the biggest source of exergy destruction in a Steam Power Plant’s system, so there is a big opportunity to increase the efficiency in performance. Therefore the bigger efficiency in boiler’s performance, the lower production cost for fuel consumption in industry. The average score of exergy efficiency and energy efficiency in boiler are each 71, 84% and 72, 40%. Research has resulted that heat exchanger gives the biggest contribution to the exergy destruction’s rate, that is 12, 02 % and combuster also gives contribution to the exergy destruction’s rate in the amount of 8,45 %. Therefore the total of exergy destruction’s rate in boiler is 83,771 MW from the entry exergy which is 409, 3061 MW. Other important point is the air temperature. It has became factor which affects the score of exergy destruction rate and exergy efficiency in combustor, while steam mass flow rate and generator output power are factors which influence the score variation of efficiency of total exergy, efficiency of total energy, the rate of total destruction, efficiency of heat exchanger exergy and the destruction of heat exchanger exergy rate.